Strategi dan Optimalisasi Instagram sebagai Media Layanan Informasi Publik oleh PPID Kota Semarang - Diasicha, Alvais Ardiansyah; Khotimah, Nurul (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study aims to analyze the optimization of the use of Instagram social media by PPID Semarang City in providing public information services. Instagram, as a popular social media platform, has great potential to increase access and transparency of information to the public. The method used in this study is content analysis of Instagram posts by PPID Semarang City in a certain period. The main focus of the analysis is the type of content shared, the frequency of posting, and the level of interaction with the public, including likes, comments, and shares. The results of the study show that although Instagram is used effectively to disseminate information about government policies, programs, and public services, public interaction is still relatively low. This shows that although the information presented is quite informative, it is less able to attract attention and encourage public participation. This study concludes that in order to increase the effectiveness of Instagram as a means of public information services, there needs to be an improvement in terms of content strategies that are more interesting, interactive, and encourage active community involvement. Thus, Instagram can be more optimal in increasing transparency and communication between the government and the public.